Penerapan Model Project Based Learning (PjBL) terhadap Kemampuan Literasi Sains dan Hasil Belajar Peserta Didik pada Pembelajaran IPA di Sekolah - Karmana, I Wayan (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
Scientific literacy is a very important skill for students to have and needs to be trained in classroom learning activities using an applicable approach. One learning model that can be applied to improve students' scientific literacy skills is through the application of the Project Based Learning learning model. This research aims to evaluate that research using the Project Based Learning model has a positive impact on scientific literacy abilities and student learning outcomes. The research method uses Systematic Literature Review (SLR) where researchers examine or review 50 articles from several journals via Google Scholar spanning the years 2019-2024. Data collection was carried out through the theory of inclusion and exclusion so that the final results obtained were 20 open access articles using Google Scholar. Based on the research results, it shows that the application of the Project Based Learning learning model contributes positively to improving critical thinking skills, solving problems, being able to increase literacy, and being able to improve student learning outcomes. This ability to have a positive impact will later become students' initial capital in developing affective, cognitive and psychomotor skills in science learning activities at school.